Recognizing the Effects of Language Mode on the Cognitive Advantages of Bilingualism - Yu, Ziying; Schwieter, John W. (Frontiers in Psychology, 2018)
For bilinguals, it is argued that a cognitive advantage can be linked to the constant management and need for conflict resolution that occurs when the two languages are co-activated (Bialystok, 2015). Language mode (Grosjean, 1998, 2001) is a significant variable that defines and shapes the language experiences of bilinguals and consequently, the cognitive advantages of bilingualism. Previous work, however, has not sufficiently tested the effects of language mode on the bilingual experience. In this brief review, we discuss the significance of language mode in bilingual work on speech perception, production, and reading. We offer possible explanations for conflicting findings and ways in which future work should control for its modulating effects.